Treetop shelter of a neotropical river otter cub (Lontra longicaudis - Carnivora: Mustelidae) in an Amazonian flooded forest - Santos, Pedro Manuel Ribeiro Simões dos; Kinupp, Valdely Ferreira; Silva, Alexandre Coletto da (Acta Amazonica, 2007)
The finding of a Neotropical river otter (Lontra longicaudis) cub occupying a shelter in a hollowed treetop is reported. The observation was made in a seasonally flooded forest in Central Amazonia, during the high water peak of the annual inundation cycle. A literature review indicates that this is the first description of a shelter of the species, both in a hollowed tree and in Amazonia. This observation can indicate a strong relationship between the species' breeding cycle with the annual dynamics of Amazonian rivers. We discuss potential advantages and disadvantages of breeding when water level is high.
Abrigo em copa de árvore de filhote de lontra neotropical (Lontra longicaudis - Carnivora: Mustelidae) em floresta inundável amazônica
Keywords: Amazon; Flooded Forest; Lontra Longicaudis; Shelter Use; Seasonal Water Level Variation; Amazônia; Floresta Inundada; Lontra Longicaudis; Uso De Abrigo; Variação Sazonal Do Nível Da Água